Odilo Globocnik, Hitler's man in the East - Poprzeczny, Joseph (McFarland, 2004)
"Odilo Globocnik, a collaborator of Adolf Hitler and Heinrich Himmler, was responsible for the deaths of at least 1.5 million people in three Nazi camps in occupied Poland: Treblinka, Sobibor, and Belzec. Along with Rudolf Hoss, Globocnik may be named as one of the first industrial-style killers in history. Betraying his homeland by conspiring with Hitler to destroy Austria's independence, he played a pivotal role in Aktion Reinhardt, directing the entire program from early 1942 until September 1943. By the winter of 1943 nearly all of the Jews of Globocnik's Lublin Distrikt had been exterminated, leaving only skilled laborers used in Globocnik's industrial conglomerates. His ethnic cleansing teams, assisted by Ukranian policing units, also cleared the Polish peasant farmers from the Zamosc Lands." "Very little has been published on Globocnik, most especially the four years he spent in Lublin. This authoritative biography, relying on exhaustive research including interviews and primary documents, details every aspect of his life. Rare photographs, many from the collection of Irmgard Rickheim, Globocnik's lover, complement the text."--BOOK JACKET.